Experience of using subacromial balloon in combined treatment of patients with rupture of the rotator cuff - Nikolay V. Zagorodni; Evgeniy A. Belyak; Fedor L. Lazko; Alexander A. Kubashev; Aleksey P. Prizov; Maxim F. Lazko; Igor V. Grigoryev; Timofey O. Skipenko; Alexandra R. Zakirova (Гений oртопедии, 2019)
Introduction Rotator cuff tears is still a complex and unresolved problem, which solution requires a comprehensive approach and choosing the optimal way of treatment. Frequently, the results of surgical treatment do not satisfy both patient and surgeon. Objective Improve the results of treatment of patients with rotator cuff ruptures of the shoulder. Material and methods Results of arthroscopic treatment of rotator cuff tears in 15 patients (mean age, 54 ± 4 years) with combined technique are presented. None of the cases had severe muscle atrophy of the rotator cuff (supra- and infraspinatus muscles), according to Goutallier classification less than 3 grade. All patients underwent shoulder arthroscopy with rotator cuff repair by single or double row stitching and subacromial balloon InSpace implantation. Results The mean score according UCLA scale before the operation was 16 ± 2 (13–18), the mean score 12 months after the operation was 30 ± 3 (26–35); in most cases good and excellent results were obtained. Conclusion Preliminary results characterize the proposed method as a relatively easy, law-traumatic and effective procedure for pain relief and shoulder function recovery in this group of patients.